Crude Glycerol Increases Neutral Detergent Fiber Degradability and Modulates Rumen Fermentative Dynamics of Kikuyu Grass in Non-Lactating Holstein Cows Raised in Tropical Conditions - Valencia-Echavarria, Diana Marcela; Granja-Salcedo, Yury Tatiana; Noriega-Marquez, Jorge Guillermo; Valderrama, Luis Alfonso Giraldo; Vargas, Julián Andrés Castillo; Berchielli, Telma Teresinha [UNESP] (MDPI, 2024)
This study evaluated the effects of increasing levels of crude glycerol (CG) on the effective degradability of neutral detergent fiber (EDNDF) in Pennisetum clandestinum Hochst. Ex Chiov (kikuyu forage) and ruminal fermentation parameters in grazing dairy cows. Four non-lactating cannulated Holstein cows were used in a 4 × 4 Latin square design. Treatments consisted of CG infusion in the rumen at the following levels: 0 (G0), 500 (G500), 1000 (G1000), and 1500 (G1500) g/animal/day. Two kikuyu forages harvested (D) at 35 (DR35) and 45 (DR45) days of regrowth were incubated in the rumen for 72 h. The infusion of CG into the rumen increased (p < 0.05) EDNDF in both incubated forages. Total volatile fatty acids (VFAs) and pH values in the ruminal fluid were unaffected (p > 0.05) by the infusion of CG. However, propionate and butyrate molar proportions increased (p < 0.05) at the expense of acetate at all CG levels. In addition, the NH3-N levels decreased (p < 0.05) by approximately 20% with the infusion of 1000 and 1500 g of CG. In conclusion, supplementation with CG increases ruminal EDNDF, improving rumen fermentation dynamics in cows grazing kikuyu forage under tropical conditions. This greater EDNDF was achieved for both harvesting times.
Keywords: biofuel; fermentative dynamics; sugar alcohol; tropical pasture